Increasing opportunities for obstetric fistula case detection and treatment by using a multifaceted approach – the case of Kalungu district –Uganda - Tumusiime, Molly; Kaduyu, Paul; Kanakulya, Hassan; Mukisa, Rose; Arnoff, Elly; Tripathi, Vandana (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To identify fistula treatment barriers and increase treatment access in Kalungu, Uganda. Methods: Responding to treatment barriers identified through formative research, the USAID-funded Fistula Care Plus (FC+) Project is implementing a comprehensive intervention to address fistula treatment barriers. The intervention utilizes multiple communication channels (free fistula screening hotline, health workers, and community agents), a consistent screening algorithm for fistula screening, and a transportation voucher to enable positively-screened women to travel to and from the fistula treatment facility. Results: FC+ trained and oriented 42 health workers and 275 community agents across Kalungu District to raise awareness and identify suspected fistula cases; trainees were provided with fistula hotline advertisements and data collection and referral tools. Thirty drivers were also trained and oriented on the transportation voucher system. From July 2017 to July 2018, the hotline received 120 callers from Kalungu; 88 screened positively. 37 women from Kalungu used the voucher system for free transport. In all, 51 women from Kalungu were referred to the fistula facility through the intervention’s referral channels. Facility records indicate that the number of women seeking fistula treatment from Kalungu District increased during the intervention period compared to the prior year. Conclusions: Applying client-centered communication, screening, referral, and transportation mechanisms enabled FC+ to address treatment barriers in Uganda. This approach may be replicated in other settings where the backlog of unidentified/untreated fistula cases persists.